Valorization of Oil Palm Empty Fruit Bunches into Sulfonated Carbon Catalysts for Esterification of Vegetable Oil - Saragih, Gimelliya; Purwandari, Vivi; Silitonga, Nelson; Abdillah; Sitanggang, Yenny; Zai, Liver; Mukhtissiarni (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2025)
This research explores the physicochemical characteristics of activated and sulfonated carbons derived from palm empty fruit bunches (OPEFB) as renewable raw materials, and assesses their catalytic performance in the esterification of waste cooking oil (WCO) for biodiesel synthesis. Activated carbon was sulfonated via exposure to high-concentration sulfuric acid (H₂SO₄) at 7%, 10%, and 13%, facilitating the incorporation of –SO₃H groups. A range of analytical techniques, including TGA, DTA, FTIR, BET, and SEM, was employed to characterize the synthesized materials. Among the synthesized catalysts, the sulfonated carbon with 10% acid treatment (SA 10%) exhibited the most favorable characteristics: demonstrated a surface area of 41.895 m²/g and retained its structure under thermal stress, and a strong presence of sulfonic functional groups. Esterification tests at 65 °C for 2 hours showed a maximum yield of 43.28% using 3 g of SA 10%, while 5 g resulted in a lower yield of 30.32%. The results demonstrate that SA 10% is a promising eco-friendly heterogeneous catalyst for converting low-cost, waste-based feedstocks into biodiesel under mild reaction conditions.